Screening and identification of Paenibacillus polymyxa GRY-11 and its biological control potential against apple replant disease - Li, Xiaoxuan; Wang, Jian; Lv, Yi; Zhao, Lei; Jiang, Weitao; Lv, Jinhui; Xu, Xin; Yu, Yajing; Liu, Yusong; Chen, Xuesen; Yin, Chengmiao; Mao, Zhiquan (Folia microbiologica, 2025)
Apple replant disease (ARD) is a significant factor restricting the healthy development of the apple industry. Biological control is an important and sustainable method for mitigating ARD. In this study, a strain of Paenibacillus polymyxa GRY-11 was isolated and screened from the rhizosphere soil of healthy apple trees in old apple orchards in Shandong Province, China, and the effects of strain GRY-11 on soil microbial community and ARD were studied. The result showed that P. polymyxa GRY-11 could effectively inhibit the growth of the main pathogenic fungi that caused ARD, and the inhibition rates of the strain against Fusarium moniliforme, Fusarium proliferatum, Fusarium solani, and Fusarium oxysporum were 80.00%, 71.60%, 75.00%, and 70.00%, respectively. In addition, the fermentation supernatant played an active role in suppressing the growth of pathogenic fungi. The results of the pot experiment showed that the bacterial fertilizer of the GRY-11 promoted the growth of Malus hupehensis seedlings, improved the activity of protective enzymes in plant roots, enhanced the soil enzyme content, and optimized the soil microbial environment. In general, the GRY-11 can be used as an effective microbial preparation to alleviate ARD. Our study offers novel perspectives for the prevention of ARD.
Keywords: Čína; houby; Soil Microbiology; Fusarium; rhizosféra; Fusarium spp.; China; Plant Roots; Biological Control Agents; Fungi; biologická kontrola škůdců; kořeny rostlin; Biologics; Malus; půdní mikrobiologie; nemoci rostlin; Rhizosphere; Microbial community; biologická ochrana; Antibiosis; Paenibacillus polymyxa GRY-11; Paenibacillus polymyxa; Pest Control, Biological; antibióza; Plant Diseases